Chapter 8 Pandemics and national pride: collecting and curating the history of HIV/ AIDS - Parry, Manon S. (Manchester University Press, 2022)
In recent years there has been a resurgence of museum exhibitions on the history of HIV/AIDS. While many assumed that there was enough awareness of the historical significance of this new disease to ensure the careful collection and conservation of relevant material, it is increasingly clear that a narrow range of items have been saved. As historians and curators turn to these holdings for analysis and exhibition, they find that archival and museum collections inadequately represent the impact of HIV/AIDS across diverse groups and places. This chapter considers some of the factors that have shaped museum responses to HIV/AIDS, from the accession of objects to the framing of narratives. It discusses the role of national contexts and pays close attention to the role of Dutch self-image in the framing of HIV/AIDS history there as a story of consensus and success, and the implications of this for museums and exhibitions in the Netherlands. Analysis draws on ongoing discussions with Dutch curators and a workshop with curators from museums across Europe, as well as an exhibition in Amsterdam at the International AIDS Society conference there in July 2018. This chapter highlights some of the issues that have limited museum collections and explores the potential consequences for public history. It argues that the current situation is problematic not only because archives and museum objects fuel inaccurate perceptions of the past about who was as risk and why, but also because these histories feed into responses to HIV/AIDS - and Covid-19 - in the present.